Police in ferment - Ghosh, S.K. (New Delhi, 1981)
The National Police Commission is on the job. But this is a task that possibly goes beyond the Po lice Commission. Society must demand genuine and meaning ful reform and lay the basis or a new tradition.
Keywords: Police - India